Skin hyperreactivity of Behcet's patients (pathergy reaction) is also positive in interferon alpha-treated chronic myeloid leukaemia patients, indicating similarly altered neutrophil functions in both disorders - (:unkn) unknown (OXFORD UNIV PRESS, 1998)
Typical manifestations of Behcet's disease (BD) and a positive pathergy reaction were observed in a few patients with chronic myeloid leukaemia (CML) on interferon alpha (IFN-alpha) therapy and the significance of this observation was assessed in a prospective study. The skin pathergy test was applied to 15 patients with CML prior to IFN-alpha: therapy, 29 patients with CML following IFN-alpha therapy and 30 patients with ED. Twenty-five patients with inflammatory arthropathies (IA), 20 patients with recurrent oral ulcers (ROU), 23 patients treated with IFN-alpha for various disorders and 20 normal individuals were also studied as control groups. The pathergy reaction was positive in nearly a quarter of IFN-alpha-treated CML cases (24%) as well as one-half of the patients with ED (50%. All CML patients prior to IFN-alpha treatment and all patients using IFN-alpha for other diseases were negative for the pathergy reaction. These results may indicate a similarly altered neutrophil function in both ED and IFN-alpha-treated CML patients.
Keywords: Behcet's disease; chronic myeloid leukaemia; neutrophil function; pathergy reaction; CHRONIC MYELOGENOUS LEUKEMIA; DISEASE; SPECIFICITY; SENSITIVITY